An African language in the public sphere "“ the use of isiZulu on Yilungelo Lakho online platforms - Bramdeo, Aasra (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
The South African Broadcasting Corporation (SABC) is mandated as the public broadcaster to provide news content in all South Africa's official languages. While this has been a challenge on traditional broadcast platforms, online resources, such as social media pages, present an opportunity for the SABC to support the creation and sharing of content in African languages. With relatively little national news and current affairs content available online in indigenous languages, this study investigates the way that SABC News online offerings in the isiZulu language have the potential to contribute to public debates in terms of Habermas' concept of a public sphere and its adaptation to the online domain, taking into consideration scholarly critiques of its suitability in the African context. The SABC News Current Affairs programme Yilungelo Lakho serves as a case study to examine the potential for the SABC to share African-language news content online. The programme is broadcast primarily in the Nguni languages, and the online audience on Facebook often choose to respond in isiZulu or other African languages. Semi-structured indepth interviews were conducted with three members of the production team and three contributors to the Facebook page. A textual analysis of Facebook posts across 13 episodes, with a total of 497 comments from 306 online contributors highlights the manner in which online interaction promotes or hampers the inclusion of isiZulu speakers in SABC News and Current Affairs discussions, rational deliberation on the SABC Current Affairs programme, and fragmentation and overlap across different online platforms. While multilingual interactions on the Yilungelo Lakho Facebook page make for complex curation, the findings suggest the need for African language content to support public discussions and point to an opportunity for the public broadcaster to fulfil its mandate.
Keywords: Zulu language; News Web sites -- South Africa; South African Broadcasting Corporation; Facebook (Firm); Social media and journalism -- South Africa; Public sphere -- South Africa; Mass media and language -- South Africa; Yilungelo Lakho